Perbandingan Pembuatan Kartu Identitas Warga Negara Indonesia dan Singapura - Nisa, Vira Khairun; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Identity cards play a crucial role in proving someone's identity in the modern era. This research compares the process of issuing national identity cards in Indonesia and Singapore, focusing on security, efficiency, speed, and reliability. Indonesia, with its large and diverse population, and Singapore, with a smaller population but high population density, demonstrate different approaches to identity card issuance. An analysis is conducted on the strengths and weaknesses of each system, including technological innovation, population coverage, inter-agency cooperation, biometric usage, and improvements in public services. Despite facing challenges such as limited infrastructure, administrative issues, and potential corruption, Indonesia continues to innovate with chip technology and inter-agency collaboration. In Singapore, an efficient identity card issuance system is supported by advanced technology, online services, and a focus on privacy. Nevertheless, challenges related to technology dependence, privacy issues, accessibility, administrative errors, and costs remain concerns. Nonetheless, this research provides valuable insights for the development of public administration systems in other countries